Study of the multiple incorporation of modified nucleotides into the growing DNA strand - O. S. Volkova; A. V. Chudinov; S. A. Lapa (Тонкие химические технологии)
Objectives. This study investigated the substrate properties of the modified derivatives of triphosphates of purine and pyrimidine deoxynucleosides (5-propynyl-2’-deoxyuridine-5’-triphosphate, 5-propynyl2’-deoxycytidine-5’-triphosphate, 5-methyl-2’-deoxycytidine-5’-triphosphate, and N6-methyl-2’-deoxyadenosine-5’-triphosphate) during their simultaneous incorporation in enzymatic reactions (polymerase chain and primer extension reactions).Methods. The real-time polymerase chain and primer extension reactions were used to study the substrate efficiency of modified deoxynucleotide triphosphates. Various pairwise combinations of modified derivatives were used; specially designed synthetic DNA fragments and libraries for the Systematic Evolution of Ligands by Exponential Enrichment technology were used as templates. Reactions were conducted using DNA polymerases: Taq, Vent (exo-), DeepVent (exo-), and KOD XL.Results. In each case, a pair of compounds (modified dUTP + dCTP, dUTP + dATP, and dCTP + dATP) was selected to study the simultaneous incorporation into the growing DNA strand. The most effective combinations of nucleotides for simultaneous insertion were dU and dC, having 5-propynyl substitution. The Vent (exo-) DNA polymerase was found as the most effective for the modified substrates.Conclusions. The selected compounds can be used for the enzymatic preparation of modified DNA, including aptamers with extended physicochemical properties.